THE IMPACT OF HUMAN DEVELOPMENT ON FOOD SECURITY IN ARAB COUNTRIES. PERSPECTIVE FROM A PANEL-ARDL ANALYSIS - Hadjira Larbi Cherif; Amina Badreddine; Azzeddinne Sabri (International Journal of Innovative Technologies in Social Science, 2024)
The purpose of this paper is to examine the relationship between the Human Development Index (HDI) and food security in Arab countries over the period of 2012-2022. Employing Panel Autoregressive Distributed Lag (PANEL-ARDL) cointegration model, the study examines how the Human Development Index (HDI) affects the General Food Security Index GFSI for seven Arab countries. The empirical results provide evidence of cointegration and long run equilibrium between the HDI and GFSI. Increased values of HDI make predictions of better food security possible through factors like education, health, and income. The error correction term indicates rapid adjustment to long-term equilibrium. While analysing the data the study concludes that HDI shows positive relationship with food security emphasizing on the need to human develop the food security in the Arab region.